Energies of Space In-Between - Clas D.S. Steinmann (Oz, 1987)
Wind, fragrance and sound< /br> Time< /br> Movement< /br> Hovering and at ease< /br> Openness and tightness< /br> Certainty and vulnerability< /br>The Mysterious, obscure, unexplicable,< /br> incomprehensible, mystical.